Electrolytes : supramolecular interactions and non-equilibrium phenomena in concentrated solutions /: supramolecular interactions and non-equilibrium phenomena in concentrated solutions. (2014) - Aseev, G. G (Georgiĭ Georgievich)
No abstract available